Linking the dots: ORCID in the publishing workflow - Cheng, Chieh-Chih Estelle; Marín-Arraiza, Paloma (Septentrio Conference Series, 2022)
One of the key concepts in open science is sharing, but this may not be in place without open research infrastructure. Openness is one of the key ORCID values, and we work with the global community and partners to build and sustain a technology infrastructure that not only allows the sharing of research information between systems but also enables the open creation of linkages between researchers, research institutions, publishers, and funding organisations. The global publishing community is one of the earliest ORCID adopters and has been one of the most significant contributors to the data in the ORCID Registry. Although substantial publishers have implemented ORCID into the publishing workflow, their practices vary due to various reasons, such as the capacities of the publishing systems they use or their levels of support for ORCID. To maximise the benefits of ORCID in the publishing workflow will require publishers to follow the best practices of ORCID adoptions. By implementing deeper workflows with ORCID, researchers and organisations benefit from ‘trust markers’ to advance trusted research worldwide and improve the integrity of the research process. This is achieved through affiliation data added by the institutions, contributions on the researcher records that other publishers or repositories have added, and funding history or additional data such as other person identifiers and organisation identifiers. This trusted data can then be used further downstream in the community’s workflows.